2018
DOI: 10.1155/2018/6964828
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Traffic Composition on Freeway Crash Frequency by Injury Severity: A Bayesian Multivariate Spatial Modeling Approach

Abstract: This study sets out to investigate the effects of traffic composition on freeway crash frequency by injury severity. A crash dataset collected from Kaiyang Freeway, China, is adopted for the empirical analysis, where vehicles are divided into five categories and crashes are classified into no injury and injury levels. In consideration of correlated spatial effects between adjacent segments, a Bayesian multivariate conditional autoregressive model is proposed to link no-injury and injury crash frequencies to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 35 publications
0
15
1
Order By: Relevance
“…The freeware WinBUGS provides a friendly programming environment for conducting Bayesian inference on the parameters in the CAR model, which does not have an easily calculable likelihood function. Besides, the multivariate version of the CAR model is the state-of-the-art method for multivariate spatial modeling crash frequency by injury severity [22,23,24], crash type [25], transportation mode [26], or crash period [27].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The freeware WinBUGS provides a friendly programming environment for conducting Bayesian inference on the parameters in the CAR model, which does not have an easily calculable likelihood function. Besides, the multivariate version of the CAR model is the state-of-the-art method for multivariate spatial modeling crash frequency by injury severity [22,23,24], crash type [25], transportation mode [26], or crash period [27].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Unobserved heterogeneity and spatial correlation were addressed, and the results helped to prioritize area-wide safety initiatives and programs. Besides bivariate regression models, different multivariate regression models, for example, multivariate tobit analysis [29][30][31][32], Bayesian multivariate approach [33,34], multivariate spatial or/and temporal models [35][36][37][38][39], and mixture of abovementioned models, have been presented to address correlation and unobserved heterogeneity among injury severities.…”
Section: Introductionmentioning
confidence: 99%
“…The curvature has been found positively correlated with accident occurrence [24,37,54]. Wen et al [56] found that the curvature was positively associated with the property damage accidents only. Haq et al [31] found a decreasing impact of horizontal curve radius on the truck related accidents.…”
Section: Geometric Design Elementsmentioning
confidence: 95%
“…Many researchers [17,18,40,41,43,46,55] found the expressway segment length to be positively correlated with number of accidents. Wen et al [56] used variable daily vehicle kilometer travel (DVKT) and found it positively associated with accident frequencies. Similarly, Wen et al [11] used variable monthly vehicle kilometer travel (MVKT) and found positively correlated with the accident frequency.…”
Section: Exposurevariablesmentioning
confidence: 99%